2013
DOI: 10.1038/jid.2012.292
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Improves Acne in Humans by Modulating Intracellular Molecular Targets and Inhibiting P. acnes

Abstract: Acne vulgaris is a highly prevalent skin disorder characterized by hyperseborrhea, inflammation, and Propionibacterium acnes overgrowth. Only isotretinoin and hormonal therapy reduce sebum production. To identify a new drug candidate that modulates sebum, we examined the effects of EGCG, the major polyphenol in green tea, on human SEB-1 sebocytes and in patients with acne. In SEB-1 sebocytes, we found that EGCG reduced sebum by modulating the AMPK-SREBP-1 signaling pathway. EGCG also reduces inflammation by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 60 publications
2
110
0
7
Order By: Relevance
“…Epigallocatechin-3-gallate, the major polyphenol in green tea, was found to reduce sebum by modulating the AMPK-SREBP-1 signaling pathway and inflammation through suppression of NF- κ B and AP-1 pathways. These findings were supported by an 8-week randomized, split-face, and clinical trial where the molecule significantly improved acne and was found to be well tolerated [123]. …”
Section: Plants Having Antiacne Potentialmentioning
confidence: 74%
“…Epigallocatechin-3-gallate, the major polyphenol in green tea, was found to reduce sebum by modulating the AMPK-SREBP-1 signaling pathway and inflammation through suppression of NF- κ B and AP-1 pathways. These findings were supported by an 8-week randomized, split-face, and clinical trial where the molecule significantly improved acne and was found to be well tolerated [123]. …”
Section: Plants Having Antiacne Potentialmentioning
confidence: 74%
“…In our previous study, we discovered that epigallocatechin-3-gallate improves acne by modulating multiple pathogenic factors, including hyperseborrhea, inflammation, and P. acnes overgrowth (Yoon et al, 2013). In spite of great efficacy in properly controlled condition, relative molecular instability of this anti-oxidant could be affected by various external factors including solvent, pH, temperature, ionic strength, and oxidative stress (Proniuk, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…After 8 weeks of treatment, biomarker levels were not changed by green tea [80]. Another trial reported a beneficial impact of topical EGCG treatment on acne vulgaris, which might be at least in part due to anti-inflammatory effects [81]. Interestingly, in 2006, a green tea extract was approved as a prescription drug for the topical treatment of genital and anal warts (condylomata acuminata).…”
Section: Plant-derived Compounds Tested In Clinical Trialsmentioning
confidence: 99%